The Palestinian issue: a Malaysian perspectives (1957-2003) - Robani, Anidah (IIUM Press, 2009)
In the contemporary world, the Palestinian Issue still remains explosive and unresolved. Its resolution is an urgent necessity as well as a major international concern. This is particularly so to all Muslims who view it not merely as a regional or an Arab problem, but more importantly a paramount religious issue. This sentiment is indeed shared by Malaysia.